Genetic of Salak Pondoh, Gading Varieties and Its Hybrids Based on RAPD Markers - Nandariyah Nandariyah; Parjanto Parjanto; Pinaka Pinasti Ratu (Journal of Biodiversity and Biotechnology, 2021)
A molecular marker of parent and offspring is used to find fast and accurate markers influenced by DNA isolation and amplification. This research aims to find the most suitable DNA isolation and DNA  amplification methods. This study used four DNA isolation methods; namely IM01, IM02, IM03, and IM04. DNA amplification used ten protocols (AP01, AP02, AP03, AP04, AP05, AP06, AP07, AP08, AP09, and AP010). The results of the research showed that the most suitable DNA isolation method for salak was  IM0, and the most suitable DNA amplification for salak was AP04 that produces the highest value of DNA bands. Keywords: DNA isolation; DNA amplification; hybrids.